MENINGKATKAN KUALITAS HIDUP MASYARAKAT DESA GADUNG MAS MELALUI PENGEMBANGAN PROGRAM PENCEGAHAN STUNTING - Fadlah, Muhammad; Gusnaldi, Fauzi; Khalipatul Aulia, Baiq; Fauziah, Maelani; Nurus Sifak, Syarifa; Aminah, Sofiatul; Naufal Nurrafiq, Alif; Zahran Suyan WImala, Zein; Lanang Pamungkas, M. Rafly; Pancawati Martiningsih, Rr.Sri (Jurnal Wicara, 2025)
Stunting is a serious public health issue in Indonesia, including in Gadung Mas Village, Sakra Barat District, East Lombok Regency, where the prevalence reaches 25%. The main causes include lack of nutrition, poor socio-economic conditions, and low awareness of health and nutrition. To address this issue, KKN students from Mataram University conducted a stunting prevention program, which included parenting and nutrition education, supplementary feeding (PMT), and child growth monitoring at the Posyandu (integrated health post). The education sessions aimed to improve parents' and pregnant women's understanding of the importance of proper nutrition during pregnancy and early childhood. The PMT program used local food sources such as moringa leaves to improve the nutritional status of children and pregnant women. Meanwhile, the Posyandu played a role in monitoring children's growth and providing nutrition education for parents. The results showed that community-based interventions effectively increased awareness of balanced nutrition and encouraged healthier feeding practices. Positive responses from the community and health volunteers (Posyandu cadres) indicate the potential for program sustainability in reducing stunting rates. This approach is expected to continue and expand to improve children's quality of life in Gadung Mas Village and surrounding areas.